Highly Sensitive Composite Foam Bodily Sensors Based on the g-Putty Ink Soaking Procedure - Coleman, Jonathan; Boland, John (My University, 2021)
Electrically conductive composite materials are highlighted as a potential tech path toward future flexible devices for wearable health technologies. To be commercially viable, these materials must not only be mechanically soft, highly sensitive to deformation, and report a sustainable signal but also utilize manufacturing methods that facilitate large-scale production. An ideal candidate for these envisioned technologies is the viscous, electromechanically sensitive composite material g-putty. Inks based on g-putty here are shown to transform a commercial polymer foam into a sensitive strain sensing material through a simple, scalable soaking procedure. Foam composites reported here have sensitives as high as ∼20 in terms of compressive strain and ∼0.4 kPa–1 with respect to applied compressive stress; both values being comparable to the parent g-putty material. Through g-putty’s self-adhering nature, the foams used acted as an elastic scaffolding that aided in overcoming many of the hysteresis effects associated with g-putty without the need for further encapsulation methods. From this, these composite foams were demonstrated to have a sustainable signal that allowed for effective impact and vital sign sensing.
PUBLISHED
cited By 0
Keywords: Graphene; Ink; Composite; Foam; Strain sensing; Bodily sensing; Smart materials; Pulse